Oral candidiasis and cigarette, tobacco, alcohol, and opium consumption in Rafsanjan, a region in the southeast of Iran - Parvin Khalili; Atekeh Movagharipoor; Farimah Sardari; Fatemeh Movaghari Pour; Zahra Jamali (BMC, 2023)
Abstract Background We investigated the association between oral candidiasis prevalence and cigarette, tobacco, alcohol, and opium consumption in Rafsanjan, a region in the southeast of Iran. Methods This cross-sectional study was conducted using the data of Oral Health Branch of Rafsanjan Cohort Study (OHBRCS) as a part of the Rafsanjan Cohort Study (RCS). RCS included in Prospective Epidemiological Research Studies in IrAN (PERSIAN) was begun in 2015 in the Rafsanjan. A full-mouth examination was done by trained dental specialists. Oral candidiasis was diagnosed based on clinical examination. Information about cigarette, tobacco, and opium smoking and alcohol consumption were collected based on data from self-reported questionaries. Univariate and multivariate dichotomous logistics regression were used to assess the association between oral candidiasis and cigarette, tobacco, alcohol, and opium consumption. Results Among 8682 participants with mean age of 49.94 years, the prevalence of oral candidiasis was 7.94%. There was a direct association between cigarette smoking in current and former cigarette smokers with an increased odds of oral candidiasis (OR: 3.26, 95% CI: 2.46-4.33 and OR: 1.63, 95% CI: 1.18-2.25 respectively) in fully adjusted models. There was a dose-response relationship between the odds of oral candidiasis and dose (OR: 3.31, 95% CI: 2.38-4.60), duration (OR: 2.48, 95% CI: 2.04-3.95) and number (OR: 3.01, 95% CI: 2.02-4.50) of cigarette smoking in the 4th quartile compared to reference group. Conclusions A dose-response relationship was shown between cigarette smoking and increased odds of oral candidiasis.